Reference values for 2‐dimensional and M‐mode echocardiography in Friesian and Warmblood horses - Vernemmen, Ingrid (J Vet Intern Med, 2020)
BACKGROUND: Echocardiographic reference intervals for Friesian horses are poorly described. OBJECTIVES: To obtain reference intervals for echocardiographic measurements in Friesians and compare these with Warmbloods. ANIMALS: One hundred healthy adult Friesians and 100 healthy adult Warmblood horses. METHODS: Cross‐sectional study. Two‐dimensional and M‐mode echocardiographic images were obtained. Echocardiographic measurements, including size, area, and volumetric measurements of left atrium, left and right ventricle, aorta, and pulmonary artery, were performed. Measurements were compared between the 2 breeds using an independent samples t test with Bonferroni correction for multiple comparisons. RESULTS: Reference ranges for standard echocardiographic measurements in Friesians were obtained. Several left ventricular measurements were significantly smaller in Friesians compared to Warmbloods, such as the left ventricular end‐diastolic volume using the 4‐chamber modified Simpsons' method (99.85% confidence interval for the difference [CI] = −245 to −63). Also the right ventricular end‐diastolic and peak‐systolic internal diameter were smaller in Friesians (99.85% CI = −1.33 to −0.6 and 99.85% CI = −1.54 to −0.76, respectively). Fractional shortening (99.85% CI = 0.61‐6) and ejection fraction (99.85% CI = 0.21‐4.6) were significantly larger. No structural effects of systemic hypertension, such as concentric hypertrophy, were detected. CONCLUSIONS AND CLINICAL IMPORTANCE: Our study provides reference intervals for echocardiographic measurements in Friesians useful in a clinical setting. In general, the left ventricular dimensions in Friesians were significantly smaller compared to Warmbloods, emphasizing the need for breed‐specific reference intervals.